Rheological Properties of Cement-Modified Asphalt Binders - Al-Khateeb, Ghazi; Ghuzlan, Khalid; Ismail, Mohammed; Shabib, Ahmad; Naeem, Marwan; Elbaz, Yousef (Frontiers in Built Environment, 2022)
Asphalt pavements are subjected to major distresses like fatigue, rutting, and low-temperature cracking due to repeated traffic loading and climatic conditions. The modification of the asphalt binder (a major component of an asphalt paving mixture) using additives helps in minimizing the possibility of pavement distresses. The cement additive was used in this study at cement-to-asphalt (C/A) percentages of 0, 10, and 20% by volume. The main objective of the study was to investigate the impact of C/A percentage, temperature, and loading frequency on the rutting resistance of asphalt binders using statistical analysis. Two aging conditions were also used: unaged condition and short-term aging condition in the rolling thin-film oven (RTFO). The dynamic shear rheometer (DSR) test was used to characterize the asphalt binders at ten loading frequencies (0.1, 0.3, 0.6, 1, 1.59, 3, 5, 7, 8, and 10 Hz) and four temperatures (58, 64, 70, and 76°C). These combinations were used to cover a wide range of combined conditions and to follow the high-temperature range for the Superpave performance grade (PG) system. Multiple statistical analyses [the one-way analysis of variance (ANOVA) and correlation tests] were performed to identify the relation between the tested variables and the rutting parameter (G*/sinδ). Findings of the study have shown that the loading frequency has a significant effect on the rutting parameter for unaged and RTFO-aged asphalt binders under different temperatures and using different C/A percentages. Regression analysis was conducted to depict an accurate model that can predict the rutting parameter (G*/sinδ) for each aging condition. Based on the regression analysis, nonlinear power models were developed for the rutting parameter of four groups: unaged unmodified, unaged cement-modified, RTFO-aged unmodified, and RTFO-aged cement-modified asphalt binders with the coefficient of determination (R2) values of 0.986, 0.986, 0.996, and 0.992, respectively. The ANOVA test results showed that the cement addition (represented by the C/A percentage) had a significant impact on the rutting parameter of cement-modified asphalt binders for both aging groups. Furthermore, the correlation tests conducted in this study showed that the temperature and loading frequency had significant effects in the predictive models of the rutting parameter of unmodified asphalt binders and that the temperature, loading frequency, and C/A percentage had significant effects in the predictive models of the cement-modified asphalt binders.